DAMPAK PERKEBUNAN KELAPA SAWIT TERHADAP PEREKONOMIAN WILAYAH DI KABUPATEN ROKAN HULU - IRSYADI SIRADJUDDIN (Jurnal Agroteknologi, 2015)
This research aims to know (1)  labor absorption of oil palm farmers; and (2) the productivity of oil palm farmers, (3) farmer perception, and (4) the palm plantation contribution to the regional income. The research was conducted in September 2013 until November 2013. Location of research in sub-districts of North Tambusai, Kunto Darussalam, Tandun, and Kabun in Rokan Hulu District. The method used interviews, questionnaires, and documentation. Sampling was done by purposive. Results of this research is the most of labor absorption in sub-district Kabun (4.22 HOK / ha), followed by North Tambusai (3.30 HOK / Ha), Kunto Darussalam (3.21 HOK / ha), and Tandun (2.99 HOK / Ha). The highest productivity of palm oil in sub-district Kabun (21.16 ton/ha/ year), followed by Kunto Darussalam (19.40 ton/ha/year), North Tambusai (15.76 ton/ha/ear), and Tandun (11,97 ton/ha/year). The most reason of farmers perception on palm plantation is marketing easier, followed by production facilities are supported, easy palm cultivation, the selling price and the income of farmers is high. The most farmers perception to use the income is education of children, followed by repair and extension the house, purchase of motor vehicles, and extend of palm plantations. The largest palm plantation contribution to the regional income is North Tambusai Sub-Distric, followed by Kunto Darussalam, Kabun, and Tandun.